PENERAPAN MODEL PEMBELAJARAN TALKING STICK DALAM MENINGKATKAN HASIL BELAJAR PAI DI SDN 192 AWOTA - Nunul Hariska; Akhmad Syahid; Maryam Ismail; Abdul Wahab; Mustamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to see how the application of the Talking Stick learning model improves the learningoutcomes of grade VI students in the subject of Islamic Religious Education (PAI) at SD Negeri 192Awota, Keera District, Wajo Regency. This study uses a Classroom Action Research (CAR) approachconsisting of two cycles, each with two meetings. A total of 36 grade VI students became the subjectsof the study. Data collection was carried out through observation, interviews, written tests, anddocumentation. Data analysis included calculating percentages and averages (means) to measurestudent activity and learning completeness. The results showed a significant increase in studentlearning outcomes after the application of the Talking Stick method. In cycle I, 21 students (58.33%)achieved learning completeness with an average score of 74.72 ("good"). In cycle II, there was anincrease in the number of students who completed to 33 students (91.66%) with an average score of85.00 ("very good"). These findings indicate that the Talking Stick method is effective in improvingthe learning outcomes of grade VI students in PAI.